Instrument Analysis of Library Service Components in Distance Education Conceptualized Library Accreditation at Universitas Terbuka - Ristiyono, Mohamad Pandu (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Library accreditation is a form of legal recognition of a library in an institution. Open university libraries that have the concept of distance education carry out library accreditation from the directorate of standardization of the National Library of Indonesia. Where there are 6 components and 103 instruments. in this paper only discusses component 3, namely the service component, where there are 19 instruments. From the discussion of library service component instruments, there are several instruments that are not suitable for open university libraries that implement distance education, namely library visitor instruments, where those who come offline are far different from conventional universities while online open university library visitors are more than 16 million. In addition, the collection lending instrument is also different, where borrowing at open universities is done virtually. In the future, there needs to be a distinction for instruments for distance education libraries and conventional university libraries.